2014
DOI: 10.1155/2014/307976
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Homozygous Mutation in the EC1/EC2 Interaction Domain of the Gap Junction Complex Connexon 26 Leads to Profound Hearing Impairment

Abstract: To date, about 165 genetic loci or genes have been identified which are associated with nonsyndromal hearing impairment. In about half the cases, genetic defects in the GJB2 gene (connexin 26) are the most common cause of inner-ear deafness. The genes GJB2 and GJB6 are localized on chromosome 13q11-12 in tandem orientation. Connexins belong to the group of “gap junction” proteins, which form connexons, each consisting of six connexin molecules. These are responsible for the exchange of ions and smaller molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…The presence of this cysteine, in addition to creating proper folding, is essential for proper performance of the ionic channel. Mutation in one of the three Cys residues in the extracellular domain of the Cx26 protein disturbs the flow of K + ions, hence ionic homeostasis, in the inner ear (BIRKENHÄGER et al, 2014;MAEDA et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of this cysteine, in addition to creating proper folding, is essential for proper performance of the ionic channel. Mutation in one of the three Cys residues in the extracellular domain of the Cx26 protein disturbs the flow of K + ions, hence ionic homeostasis, in the inner ear (BIRKENHÄGER et al, 2014;MAEDA et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Autosomal recessive genes with more than 55 different genes (http://hereditaryhearingloss.org) have been identified so far and they are responsible for about 80% of non-syndromic HL cases (CRYNS and VAN CAMP, 2004;MAEDA et al, 2009). However, in some populations, mutations in the GJB2 (Gap junction protein, GJB2, 26kDa) gene, which is located in DFNB1 locus, are responsible for half of the ARNSHL cases (BIRKENHÄGER et al, 2014). The GJB2 gene encodes connexin26 (Cx26) protein.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They form the intramolecular disulfide bridges between the cysteine residues. The disulfide bonds of the residual cysteine are between 53 and 180, 60 and 174, and also between 64 and 169 [17]. Studies on other proteins have shown that a substitution of cysteine residues would result in the destabilization of the protein structure [16].…”
Section: Connexin 26 Proteinmentioning
confidence: 99%
“…Although the translation of protein structure is completed, the resulting protein has an abnormal structure of the extracellular domain E2 [17]. This mutation occurs in a highly conserved region, which affects one of the three cysteine residues responsible for disulfide bonds, which are extremely important for the connexon-connexon interaction.…”
Section: Mutations In the Gjb2 Genementioning
confidence: 99%